You should have been nicer to my mom : a modern gothic horror - Tirado, Vincent (William Morrow, an imprint of HarperCollins Publishers, 2026)
"When Papi Ramon, the patriarch of the wealthy Abreu family dies, he gives the family one last message in the will: "One of you is el bacà, the demon that I made a deal with. Get rid of them or you will be damned." Xiomara, the uncontested favorite of Papi Ramon (and therefore the least liked in the family), watches as everyone dismisses this as the joke of a senile old man and demands the lawyer obtain the previous will Papi wrote. While the lawyer drives back to his office, a storm breaks out, forcing the entire family--Xiomara's aunts and uncles and cousins--to remain in the house. And the words of Papi's will hangs over their heads even heavier than the rain clouds. Over the course of the night, scandal after scandal is revealed to the public about the family. Suddenly a tense few hours of surviving her family turns into a vicious night of recrimination, violence, accusations...and murder. Xiomara is faced with an impossible task: uproot a demon and somehow kill it or excise the ghosts that linger within her own family. And the clock is ticking..."--Amazon.